Integral Sliding Mode Based Disturbance Observer and Control for Robust Tracking Control of Quadrotor Systems - Lim, Chaiyoon; Heo, Junseo; Chwa, Dongkyoung (Transactions of the Korean Institute of Electrical Engineers, 2022)
In this paper, an integral sliding mode disturbance observer (ISMDO)-based integral sliding mode controller (ISMC) design method is proposed for robust tracking control of the position and attitude angles of a quadrotor system with disturbances. First, the dynamics of the quadrotor system is modeled including disturbances. Second, the disturbances are estimated and compensated for by designing the ISMDO. Third, a virtual attitude angle generator is used to control to follow a desired position, and a robust controller is designed to track the desired value of the system. Finally, simulations are performed to verify the proposed control method to show that the proposed robust control method is very effective compared to the methods using only one of the ISMC and the nonlinear disturbance observer.
Keywords: Attitude angle; Disturbance control; Disturbance observer; Integral sliding mode; Integral sliding mode control; Mode-based; Observer-based; Quadrotor systems; Robust tracking control; Sliding mode controller; Disturbance observer; Integral sliding mode control; Quadrotor systems; Robust control